Psychological Correction of Young Fears Swimming Athletes - Khvatskaya, Elena; Saganovich, Elena; Olga Tiunova; Ilina, Natalia; Elena Laktionova, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2020)
The paper presents the results of a two-year study on the implementation of the complex of psychological means of the correction of age and sporting activities related fears in primary school aged swimmers. Two groups of young swimmers from the sports school «Dolphin», Saint-Petersburg took part in the first part of the study: 1) 28 athletes of primary school age (born in 2005) with average sporting experience 3.5 years; and 2) 31 teen aged athlete (born in 2003) with average sporting experience 6 years. The group of teen athletes was involved to identify the characteristics of fears with primary school aged children in swimming. 12 coaches of the sports school also took part in the survey. The efficiency of the complex of psychological correction of fears in young swimmers of primary school age was confirmed by: а) the fears intensity; b) the number of athletes in the risk group and in the groups with low and intermediate fears intensity; c) state-anxiety indicator (both for the whole group of athletes born in 2005, and separately for girls and boys); d) statistically higher skill level of young swimmers of UT-1 in 2016 compared to 2014 and 2015.